Books of classes and translations among the Arabs from The Second Century AH - Fourteenth Century AH - Alqahtani, Maha Mohammed (Journal of Humanities & Social Sciences, 2025)
This research deals with the role played by the books of layers and translations in the preservation of the history of Islamic civilization has sought to give a documented picture of the areas covered by the books of layers and translations as much as possible, which illustrates the effort made by the first Muslims in the authorship of books layers and translations , and the research aims to introduce the books of layers and translations and the statement of their types and varieties and benefit from them. I have mentioned in the first section the definition of books layers and translations and their origin, importance and stages of development until the modern era and the difference between books layers and translations, and the second section deals with the benefits of books classes and translations and their relationship to history and books classified in them.
Keywords: Biographical and Classes Books; Islamic History; Scholars’ Biographies; Ilm al-Rijal (Science of Narrators); Historical Sources